Analysis Of Aircraft Control Input To Produce 3D Continuous Descent Approach (CDA) Trajectory With PY-FME - Andryando, Ronald; Ruseno, Neno (FTK UNSURYA, 2021)
One of proposed solutions to decrease the fuel consumption of a flight is by optimizing descent trajectory using Continuous Descent Approach (CDA). The focus of this research is to analyze the aircraft inputs used in CDA with several types of trajectories (straight and turning) in 3D (Three Dimensional). The CDA concept used is based on Time and Energy Managed Operation concept where the use of idle thrust is the key point. The research will also analyze the fuel consumption of aircraft in CDA trajectory and compare it with conventional descent trajectory. The methodology on this research is simulation using a Python programming module called Py-FME with Cessna-172 aircraft data. The result concluded that thrust and elevator input have significant effect on aircraft controls to achieved CDA. The research also found that CDA could reduce the fuel consumption by 67.6%.